EFEKTIVITAS IKLAN TELEVISI UNILEVER INDONESIA MENGENAI COVID-19 - Ayu Priana; K. Y.S. Putri (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2021)
Abstract Advertising is one of the important things for advertisers to provide information to the audience. Covid-19 is a national disaster that is happening in Indonesia. This study wanted to find out the effectiveness of television commercials about Covid-19 from Unilever Indonesia entitled